(untitled) (Applied Biological Research, 2023)
The present study was aimed to study the gross anatomy of free caudal vertebrae and pygostyle of kite, pigeon and crow and compare individual vertebrae within and between the species. Twelve dead adult birds from each specie were used. The collected bones were prepared for study as per Dermestid Beetle Decomposition technique. The number of free caudal vertebrae in kite, pigeon and crow were 7, 6 and 6, respectively. The presence of bifid dorsal & ventral spine, and a distinct cranial articular process in initial segments was characteristic in kite. In pigeon, ventral spine was absent in 1st three caudal vertebrae while 6th caudal vertebra was ygostyle. In crow, ventral spine was absent in 1st two caudal vertebrae while in rest vertebrae it was tuberous. The length of transverse process in all the species was initially less, increased in middle region and reduced towards end. The last free caudal vertebra in pigeon lacked transverse process. The pygostyle was trapezoid in kite, triangular in crow and roughly quadrilateral in pigeon. The study revealed significant differences in caudal vertebrae within and between the species. The presence of cranaial articular processes and tuberculous structures suggested that free caudal vertebrae in kite were well-developed for strong catch hold to the skeletal muscles for better hunting. The pygostyle and free caudal vertebrae were more closely related in kite and crow than in pigeon.